The Brontës' Irish Background Revisited. (April 2014) - Chitham, Edward
Abstract : Interest is again being expressed in the Brontës' Irish background. A number of points can be added to the research detailed in The Brontes' Irish Background of 1986 and K. Constable's A Stranger within the Gates in 2000. An important factor is the definite date now available for Hugh Brunty's birth. Further to this, new light has been shed on the demography of County Fermanagh by the publication of the Ordnance Survey Memoirs in the 1990s and by more accessible copies of the Irish 'Tithe Applotment' and Griffith's 'Valuation' on the Internet. This article brings some of this new material forward as a contribution to the understanding of the Brontes' family heritage.